Pengaruh Penambahan Poli Vinil Alkohol (PVA) pada Enkapsulasi Minyak Kacang Kenari dalam Urea-Formaldehid untuk Aplikasi Self-Healing Coating - Reviana Inda Dwi Suyatmo; Abdussalam Topandi; Lathiefah Oktriananda Sari; Lukman Nulhakim (Jurnal Teknologi, 2023)
Self-healing coating is a method that can be used to minimize the impact of cracks on metal surfaces. Self-healing coating repairs cracks without human intervention. In microcapsule self-healing coating, there is a core material and a shell. The core material is the healing agent for surface damage, while the shell will break if a crack occurs, removing the core material. In this study, the core material used is walnut oil which belongs to the drying oil group while the shell material used was urea-formaldehyde. Poly Vinyl Alcohol (PVA) took a role as a surfactant in the microcapsule reaction. The PVA concentrations used were 0%, 3%, 4%, and 5%. The results of the microcapsule diameter test showed that 5% PVA produced microcapsules with the smallest diameter of 90.1426 microns. Based on the results of observations through a microscope, it was also seen that without the addition of PVA, the formation of microcapsule granules did not occur where the results were still agglomerated. The results of the thermal stability test using Thermo Gravimetry Analyzer (TGA) showed that the addition of PVA had no significant effect on the decomposition temperature of the microcapsule where this decomposition temperature was still under the requirements for coating applications. The results of the Scanning Electron Microscope (SEM) test also strengthen the results of microscope. Microcapsules of 5% PVA was better and do not clump when compared to 4% PVA microcapsules.